Sistem Pakar Identifikasi Penyakit Kambing Jawa Menggunakan Metode Forward Chaining - Sri Muhammad Kusumantomo; Mutaqin Akbar (Universitas Mercu Buana Yogyakarta, 2021)
Goats in the livestock business are a promising business zone. Java goats, for example, Java type goats have a very expensive price, from young Java goats to old Java goats. The Javanese goat business is indeed very profitable, but this business is not without obstacles. There are so many obstacles faced by breeders, especially those who live in villages far from animal hospitals. Thus, the method of identifying the disease of Javan goats was chosen because the symptoms of diseases commonly experienced by Javan goats are relatively easy to observe and comfortable for anyone to try. The developed application is equipped with an easy-to-use and dynamic knowledge management system. This means that experts can add, change, and delete new knowledge or provisions without having to start from scratch. The application was developed using the PHP programming language and MySQL as the information base. The inference procedure used is forward chaining, which is an inference process that starts the search from premises or input information in the form of indications leading to conclusions, namely conclusions about the disease experienced and providing solutions regarding recommendations for healing and prevention based on the observed signs. the results of 100% correspondence between the results of the identification of the expert with the identification of the application.